TREATMENT OF INGROWN TOE NAIL-COMPARISON OF PHENOLIZATION AFTER PARTIAL NAIL AVULSION AND PARTIAL NAIL AVULSION ALONE - Khan, Irshad Ali; Shah, Syed Fahd; Waqar, Shahzad Hussain; Abdullah, Muhammad Tariq; Malik, Zafar; Zahid, Muhammad Abdul (Journal of Ayub Medical College Abbottabad, 2014)
Background: Ingrown toe nail is common problem presenting to the surgeon. Partial Nail avulsion only results in recurrence of the ingrown toe nail. The aim of this study was too see the effect of phenolization in preventing recurrence after partial nail avulsion. Methods: This was a randomized controlled trial carried out at Department of Surgery, Pakistan Institute of Medical Sciences, Islamabad. This study included 100 patients (50 in each group) with ingrown toe nail presented from November 2009 to October 2010. This study compared the application of phenol after partial avulsion with partial avulsion alone in the treatment of ingrown toe nail. Results: Sixty-nine percent of the patients were males and 31% were female. The mean age in both groups was 18 years. Patient in the partial nail avulsion with application of phenol group had less pain as compared to patient with partial nail avulsion group only. Our study has shown that patient in phenol group had less post operative infection, spike formation and recurrence as compared to wedge resection group only. Conclusion: Partial nail avulsion with phenolization is better than partial nail avulsion only for the management of the in-growing toe nail. Keywords: Ingrowing toe nail, Wedge resection, Chemical matirimectomy